Molecular testing for adolescent and young adult central nervous system tumors: A Canadian guideline - Lim-Fat, Mary Jane; Macdonald, Maria; Lapointe, Sarah; Climans, Seth Andrew; Cacciotti, Chantel; Chahal, Manik; Perreault, Sebastien; Tsang, Derek S.; Gao, Andrew; Yip, Stephen; Keith, Julia; Bennett, Julie; et al. (Frontiers in Oncology, 2022)
The 2021 World Health Organization (WHO) classification of CNS tumors incorporates molecular signatures with histology and has highlighted differences across pediatric vs adult-type CNS tumors. However, adolescent and young adults (AYA; aged 15–39), can suffer from tumors across this spectrum and is a recognized orphan population that requires multidisciplinary, specialized care, and often through a transition phase. To advocate for a uniform testing strategy in AYAs, pediatric and adult specialists from neuro-oncology, radiation oncology, neuropathology, and neurosurgery helped develop this review and testing framework through the Canadian AYA Neuro-Oncology Consortium. We propose a comprehensive approach to molecular testing in this unique population, based on the recent tumor classification and within the clinical framework of the provincial health care systems in Canada.